Novel perspectives on the pharmacological treatment of thyroid-associated ophthalmopathy - Li, Zilin (Frontiers in Endocrinology, 2025)
Thyroid-associated ophthalmopathy (TAO), an autoimmune disease closely related to thyroid dysfunction, remains a challenging ophthalmic condition among adults. Its clinical manifestations are complex and diverse, and disease progression can lead to exophthalmos, diplopia, exposure keratitis, corneal ulceration, and compressive optic neuropathy, resulting in irreversible vision damage or even blindness. Traditional treatment methods for TAO, including glucocorticoids, immunosuppressants, and radiation therapy, often have limitations and side effects, making this disease problematic in ophthalmology. As a result, the development of novel targeted drugs has become a research hotspot for addressing the pathogenesis of TAO. A range of novel targeted drugs, such as teprotumumab and tocilizumab, have been successfully developed and demonstrated remarkable efficacy in relieving inflammation and managing this disease. In addition, some drug candidates and molecular targets identified in the TAO in vitro model have shown promising prospects. This article briefly reviews the potential new strategies for future clinical treatment and the progress of new drug therapies for TAO.